Analisis Efisiensi Tiga Mekanisme Pengakuan Bersalah dalam KUHAP 2025: Pasal 78, Pasal 205, dan Pasal 234 - Erfan Afandi; Roy Marthen Moonti; Ibrahim Ahmad (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
The reform of criminal procedural law through Law Number 20 of 2025 concerning the Criminal Procedure Code introduced a confession of guilt through three mechanisms spread across Article 78, Article 205, and Article 234. All three have different entry points, requirements, and examination patterns, but all lead to a brief examination. This study aims to analyze the construction and efficiency of these three mechanisms, while identifying overlaps, repetition of stages, and potential uncertainty in their application. The study uses normative legal methods with statutory, conceptual, and comparative legal approaches. The results show that Article 78 forms a written agreement mechanism between the public prosecutor and the defendant before the main case examination; Article 205 opens up the defendant's confession after peace efforts are not achieved; while Article 234 allows for a transfer to a brief examination when the defendant admits all charges when the indictment is read. Although intended to expedite the resolution of cases, these three routes are not yet fully efficient because they still go through a series of prosecution, transfer, preliminary hearing or reading of the indictment, verification of the confession, and a brief examination which in certain cases can be longer than normal trial practice. In conclusion, the primary issue is no longer defining the requirements for cases that can use a guilty plea, as these are already stipulated in the 2025 Criminal Procedure Code (KUHAP), but rather harmonizing the three mechanisms to ensure simplicity, consistency, and the absence of additional procedural layers.